2023
DOI: 10.3390/jcs7090347
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mechanical Properties of Magnesium Matrix Composites with Regression Models by Machine Learning

Song-Jeng Huang,
Yudhistira Adityawardhana,
Jeffry Sanjaya

Abstract: Magnesium matrix composites have attracted significant attention due to their lightweight nature and impressive mechanical properties. However, the fabrication process for these alloy composites is often time-consuming, expensive, and labor-intensive. To overcome these challenges, this study introduces a novel use of machine learning (ML) techniques to predict the mechanical properties of magnesium matrix composites, providing an innovative and cost-effective alternative to conventional methods. Various regres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…To develop a more reliable model for regression problems and increasing the performance from decision tree temperature prediction model, random forest (RF) regression was introduced which entailed training an ensemble of decision trees on a random subset of the bootstrap sampled data, and then combining their predictions following bootstrap aggregations [37]. In this study, the row sampling with replacement method was utilized to collect a subset (bootstrap sampled) of torch test time-temperature data (d) from the total dataset d, where d > d. Then, the subset of time-temperature data was passed through the five individual base learner trees having a constant depth of 3 in each tree.…”
Section: Random Forest Regression Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop a more reliable model for regression problems and increasing the performance from decision tree temperature prediction model, random forest (RF) regression was introduced which entailed training an ensemble of decision trees on a random subset of the bootstrap sampled data, and then combining their predictions following bootstrap aggregations [37]. In this study, the row sampling with replacement method was utilized to collect a subset (bootstrap sampled) of torch test time-temperature data (d) from the total dataset d, where d > d. Then, the subset of time-temperature data was passed through the five individual base learner trees having a constant depth of 3 in each tree.…”
Section: Random Forest Regression Modelingmentioning
confidence: 99%
“…This conventional machine learning technique was also used to simulate the modulus of elasticity and compressive stress-strain curves. The decision tree, extra tree, XGBoost, and random forest regression models' feature relevance analyses revealed that the magnesium matrix composites' reinforcing particle form had the biggest impact on their mechanical properties [37].…”
Section: Introductionmentioning
confidence: 99%